Akomodasi Komunikasi dan Rekomendasi Model Early Warning System (EWS) pada Kasus Ujaran Kebencian Berbasis Etnis di Media Sosial - Sarasati, Fitri; Jamalullail; Hamzah Ramadhan; Henry Sianipar; Tri Wahyuti (LPPM Universitas Bina Sarana Informatika, 2025)
This research analyzes the Toraja-Makassar ethnic conflict triggered by hate speech on social media and proposes a conflict prevention model based on the Early Warning System (EWS). Using Communication Accommodation Theory, research identifies forms of divergence in hate speech that widen social and cultural distances between ethnic groups. As a solution, the PRISMA EWS (Proactive Real-time Integrated Social Media Analysis Early Warning System) model is proposed which consists of four layers: monitoring-detection-analysis-response, analysis & assessment, warning system, and core system. This model is designed to detect early signs of conflict through social media analysis using machine learning, taking into account the local cultural context and involving various stakeholders. The research methodology used is qualitative with a comprehensive literature study approach to analyze the Toraja-Makassar ethnic conflict and develop a social media-based Early Warning System (EWS) model. The research results show that the PRISMA EWS model has the potential to be effective in preventing ethnic conflict on social media, although its implementation requires technological infrastructure support and intensive multi-stakeholder cooperation..